How Is Global Warming Affecting Fruit Tree Blooming? “Flowering (Dormancy) Disorder” in Japanese Pear (Pyrus pyrifolia) as a Case Study - Tominaga, Akiyoshi; Ito, Akiko; Sugiura, Toshihiko; Yamane, Hisayo (Frontiers in Plant Science, 2022)
Recent climate change has resulted in warmer temperatures. Warmer temperatures from autumn to spring has negatively affected dormancy progression, cold (de)acclimation, and cold tolerance in various temperate fruit trees. In Japan, a physiological disorder known as flowering disorder, which is an erratic flowering and bud break disorder, has recently emerged as a serious problem in the production of the pome fruit tree, Japanese (Asian) pear (Pyrus pyrifolia Nakai). Due to global warming, the annual temperature in Japan has risen markedly since the 1990s. Surveys of flowering disorder in field-grown and greenhouse-grown Japanese pear trees over several years have indicated that flowering disorder occurs in warmer years and cultivation conditions, and the risk of flowering disorder occurrence is higher at lower latitudes than at higher latitudes. Susceptibility to flowering disorder is linked to changes in the transcript levels of putative dormancy/flowering regulators such as DORMANCY-ASSOCIATED MADS-box (DAM) and FLOWERING LOCUS T (FT). On the basis of published studies, we conclude that autumn-winter warm temperatures cause flowering disorder through affecting cold acclimation, dormancy progression, and floral bud maturation. Additionally, warm conditions also decrease carbohydrate accumulation in shoots, leading to reduced tree vigor. We propose that all these physiological and metabolic changes due to the lack of chilling during the dormancy phase interact to cause flowering disorder in the spring. We also propose that the process of chilling exposure rather than the total amount of chilling may be important for the precise control of dormancy progression and robust blooming, which in turn suggests the necessity of re-evaluation of the characteristics of cultivar-dependent chilling requirement trait. A full understanding of the molecular and metabolic regulatory mechanisms of both dormancy completion (floral bud maturation) and dormancy break (release from the repression of bud break) will help to clarify the physiological basis of dormancy-related physiological disorder and also provide useful strategies to mitigate or overcome it under global warming.